Wellbeing recovery inequity following the 2010/2011 Canterbury earthquake sequence: repeated cross‐sectional studies - Annabel Begg; Lucy D'Aeth; Emma Kenagy; Chris Ambrose; Hongfang Dong; Philip J. Schluter (Australian and New Zealand Journal of Public Health, 2021)
Abstract Objective: To track population mental wellbeing following the 2010/2011 Christchurch earthquakes and after‐shocks. Methods: The Canterbury Wellbeing Survey, a cross‐sectional survey of randomly selected adults aged ≥18 years resident in Christchurch, was repeated biannually from April 2013 until June 2017 and annually thereafter. The self‐reported 5‐item World Health Organization Well‐Being Index (WHO‐5) has been elicited from April 2013. Regression analysis was employed to model WHO‐5 score patterns over time and between important socio‐demographic groups. Results: Between 1,137 and 1,482 adults participated in each survey, totalling 14,100 overall. The mean WHO‐5 significantly increased (p<0.001) from 52.4 (95% confidence interval [CI]: 51.1, 53.8) in the April 2013 survey to 60.8 (95%CI: 59.7, 61.9) in the June 2019 survey. A significant and sustained household income group disparity existed (p<0.001), even when adjusting for age, gender and ethnic differences. Conclusions: The disaster appeared to affect the mental wellbeing of all, and recovery was incremental and prolonged, taking a number of years. Those within the lowest household income group had lower mean WHO‐5 scores than their wealthier counterparts at every measured time point. Implications for public health: Recovery takes time, and pre‐existing inequities persist despite the implementation of recovery processes aimed at mitigating these risks.